2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Portal to Portal Act of 1947 [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The Portal to Portal Act of 1947 is a federal act that establishes a uniform interpretation as to what constitutes compensable working time where travel time to and from work is involved or where certain preliminary or postliminary activity can be construed as work. In general, work starts at the work site unless otherwise provided by contract, custom, or practice. This Act is an Amendment to the Fair Labor Standards Act (FLSA). This is EDIS document FE412, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.